2011
DOI: 10.1183/09031936.00181410
|View full text |Cite
|
Sign up to set email alerts
|

Targets of anti-endothelial cell antibodies in pulmonary hypertension and scleroderma

Abstract: Anti-endothelial cell antibodies (AECAs) have been identified in patients with systemic sclerosis (SSc) with and without pulmonary arterial hypertension (PAH) and in patients with idiopathic pulmonary arterial hypertension (iPAH). However, their target antigens remain poorly identified.Sera from 24 patients with SSc without PAH, 20 patients with SSc with PAH, 30 with iPAH and 12 healthy controls were collected. Target antigens were identified by two-dimensional electrophoresis and immunoblotting in protein ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(53 citation statements)
references
References 28 publications
0
51
0
2
Order By: Relevance
“…Indeed, a delicate balance between immunity and tolerance exists and any disturbance may result in chronic inflammation or autoimmunity. Several types of autoantibodies directed against antinuclear antigens, endothelial cells and fibroblasts have been found in idiopathic and scleroderma-associated PAH [70][71][72][73]. These autoantibodies seem to play an important role for endothelial cell apoptosis and for the expression of cellular adhesion molecules [74][75][76], and we encourage further studies to characterise their pathogenic importance.…”
Section: Inflammation and Dysimmunitymentioning
confidence: 65%
“…Indeed, a delicate balance between immunity and tolerance exists and any disturbance may result in chronic inflammation or autoimmunity. Several types of autoantibodies directed against antinuclear antigens, endothelial cells and fibroblasts have been found in idiopathic and scleroderma-associated PAH [70][71][72][73]. These autoantibodies seem to play an important role for endothelial cell apoptosis and for the expression of cellular adhesion molecules [74][75][76], and we encourage further studies to characterise their pathogenic importance.…”
Section: Inflammation and Dysimmunitymentioning
confidence: 65%
“…22,23 It is well known that PAH-SSc patients display circulating autoantibodies, but interestingly, it has been reported that a subset of patients with IPAH also display circulating immunoglobulin G-type autoantibodies directed against different components of the vascular wall, ECs, fibroblasts, and SMCs. [24][25][26][27] A recent study has confirmed the prevalence of anti-EC autoantibodies (AECAs) that recognize cell surface components in patients with IPAH (62% prevalence) or associated PAH (78% prevalence). 28 It is also estimated that 30% to 40% of patients with IPAH present antinuclear antibodies and that 10% to 15% of these patients have antiphospholipid antibodies.…”
Section: Adaptive Responsesmentioning
confidence: 94%
“…63 Using a proteomic approach, Dib and coworkers 25 were recently able to identify target antigens for AECAs in IPAH, which include lamin A/C and tubulin β-chain, major components of the inner nuclear membrane and microtubules, respectively. These proteins identified as targets of AECAs are ubiquitous and play key roles in different cell types in that they are involved in cell metabolism, morphology, and protein folding, but the exact role of AECAs in patients with IPAH remains unclear.…”
Section: Contribution Of Dysregulated Immunity To Pah Pathogenesis Enmentioning
confidence: 99%
“…Tertiary lymphoid tissue was described in patients with IPAH as evidence of altered immune regulation (106). Similarly, circulating autoantibodies are observed in patients with both autoimmune and idiopathic and other associated forms of pulmonary hypertension, but the role of these antibodies in the pathology is the subject of considerable investigation (107).…”
Section: Inflammation and Immune Mechanismsmentioning
confidence: 99%